2015
DOI: 10.1016/j.fuproc.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for ceria-based mixed oxides versus commercial platinum-based catalysts in the soot combustion reaction. Mechanistic implications

Abstract: The aim of this paper is to study the activities of ceria-zirconia and copper/ceriazirconia catalysts, comparing with a commercial platinum/alumina catalyst, for soot combustion reaction under different gas atmospheres and loose contact mode (simulating diesel exhaust conditions), in order to analyse the kinetics and to deduce mechanistic implications.Activity tests were performed under isothermal and TPR conditions. The NO oxidation to NO 2 was studied as well. It was checked that mass transfer limitations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
3
13
0
1
Order By: Relevance
“…CO. An effective delivery and transfer of active oxygen from the catalyst to the soot surface are the main factors governing the soot combustion under O2 alone as well [38,39].…”
Section: Fig 8 Depicts the Soot Conversions Profiles Versus Temperatmentioning
confidence: 99%
See 1 more Smart Citation
“…CO. An effective delivery and transfer of active oxygen from the catalyst to the soot surface are the main factors governing the soot combustion under O2 alone as well [38,39].…”
Section: Fig 8 Depicts the Soot Conversions Profiles Versus Temperatmentioning
confidence: 99%
“…The importance of the high efficiency of NO ↔ NO2 ↔ soot cycle has been reported by some researchers [34,[39][40][41][42][43] but mainly in the context of Pt-based catalysts. It has been demonstrated that the NO2 derived from NO oxidation would react with soot and initiate the creation of surface oxygenated complexes, (SOCs), which are more reactive than the complexes previously existing on soot's surface.…”
Section: < Near Figure 9 >mentioning
confidence: 99%
“…5,7 Diesel particulate lters (DPFs) combined with catalytic combustion of renewable technology is considered to be an efficient aer-treatment of soot oxidation; 3,5,[8][9][10] an effective catalyst with a lower light-off temperature is extremely important for DPF regeneration. 5,7,[9][10][11][12][13] Recently, CeO 2 has not only been reported to be used successfully in three-way catalysts, [14][15][16][17] but also as an excellent catalyst for soot combustion, 3,7,12,[18][19][20] because of its remarkable oxygen storage capacity (OSC) and redox property.…”
Section: -6mentioning
confidence: 99%
“…The preparation methods of CeO 2 -based catalysts mainly include coprecipitation, 3,5,7,8,12,13,22,27,30,31,39 hydrothermal, [40][41][42] citric acid complex combustion, 23 sol-gel, 2,33,43,44,46-48 solution combustion, 40,41 solid-state, 26 impregnation, 45 (inverse) microemulsion, 25,32,35 and solid-phase grinding methods. 34,35 Among them, the solid-phase grinding method is the easiest technique to control the positions of the metal atoms in the structure.…”
Section: 14mentioning
confidence: 99%
“…The reason for the addition of copper to the ceria-zirconia support, the choice of the particular formulation 2% CuO/Ce 0.8 Zr 0.2 O 2 and its inuence both on the soot combustion activities and on the mechanism were properly described elsewhere. 25,33,34 …”
Section: Introductionmentioning
confidence: 99%